Evaluation of immunochromatography and commercial enzyme-linked immunosorbent assay for rapid detection of norovirus antigen in stool samples - Pattara Khamrin (2018)
The efficiency of immunochromatography and commercial enzyme-linked immunosorbent assay (ELISA) kit (Denka Seiken Co. Ltd., Tokyo, Japan) were evaluated for rapid detection of norovirus (NoV) from stool specimens. A total of 503 stool specimens collected from infants and young children who suffered from acute gastroenteritis were tested for NoV by the NoV-immunochromatography kit, Denka ELISA kit, and by a monoplex RT-PCR method. The NoV-immunochromatography revealed 78.9% sensitivity, 96.4% specificity, and 92.4% efficiency with the monoplex RT-PCR method. The Denka ELISA kit had a sensitivity of 90.4%, specificity of 96.4%, and an efficiency level of 95%. The findings indicate that the newly developed NoV-immunochromatography kit provides the specificity equal to that of the Denka ELISA kit, even through the sensitivity of detection was lower. However, the advantage of the NoV-immunochromatography kit is less time consuming and simpler. The data show that both the Denka ELISA and the NoV-immunochromatography kits may be used as an alternative method for screening of NoV in stool samples. © 2007 Elsevier B.V. All rights reserved.